Airport competition in Brazil’s northeast region (Research, Society and Development, 2022)
Aviation growth is mainly due to the integration between national and world economies in the global era. The capital’s airports of the Brazilian Northeast were managed by a federal public company and are currently being granted to private companies, which have the premise of expanding the number of passengers. The increase in number of passengers drives competition between airports, since they must have adequate infrastructure to contain the demand. The choice by the user for an airport can be evaluated based on factors such as access mode, air fares, availability of flights and airport infrastructure. This paper aims at evaluating the choice of passengers between two airports in the Northeast of Brazil since 2014 and how this choice has been changing over the years. The binomial logit model was used to obtain the probability of choosing between airports and to evaluate the most relevant factors. The results of the study presented that availability for direct flights, preference for airlines, access time, air fares and general satisfaction of the airport fluctuated in the choice of the two airports during the study period. By evaluating the likelihood of choice, subsidies are provided to improve services considered indispensable by passengers.